If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(7r + -2) + -12 = 0 Reorder the terms: 5(-2 + 7r) + -12 = 0 (-2 * 5 + 7r * 5) + -12 = 0 (-10 + 35r) + -12 = 0 Reorder the terms: -10 + -12 + 35r = 0 Combine like terms: -10 + -12 = -22 -22 + 35r = 0 Solving -22 + 35r = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 22 + 35r = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 35r = 0 + 22 35r = 0 + 22 Combine like terms: 0 + 22 = 22 35r = 22 Divide each side by '35'. r = 0.6285714286 Simplifying r = 0.6285714286
| 7=5+2(g-4) | | -3x+6=5 | | 2(4y-3)=10 | | 2(9n-1)+12=-60 | | 8x-5-2x-12=1 | | x+.20=402 | | y+2x=X^2+4 | | F(x)=cos^3(x^2) | | 11-7x=-25 | | F+24=8 | | 5(x+4)-x=4(x+5)-1 | | -4a+(4a-5)= | | 6x^3+11x=13 | | 1+cos(8x)=4sin(2x) | | y-3=x^2+2x | | 2+2=6-6(x+4)+7x | | 2x+3(x+5)=5(x-3) | | 5-3logx=4 | | 3x=10+4y | | (6-9i)(6+9i)= | | 6x+12=118 | | 3.79=p-0.07 | | 3.79=p-0.05 | | 5(x-9)-7(3x+6)=25 | | 5(x+9)-7(3x+6)=25 | | 1+3(2)+3x=19 | | S=24+4h | | 2y^2+24x=0 | | (5x-7)-5(7x-12)+7=0 | | -7/3=x | | 4x-7=-51 | | y-8(/2)=7 |